Efikasi Diri, Motivasi dan Kepuasan Kerja Terhadap Kinerja Karyawan BPJS Kesehatan Cabang Yogyakarta - Susyana Candra Santi Dewi (Jurnal Indonesia Sehat, 2022)
Background: Resources as assets must be managed according to business needs, because this will make the organization competitive. The contribution of employees to the organization will be important, if done with effective actions and behave properly. BPJS Health employee performance is something that is important to study in order to improve employee behavior in accordance with organizational values, goals and strategies and increase employee productivity both individually and in groups. The pandemic period, which has not been completed until now, has had an influence on changes in the pattern of activity processes at the BPJS Kesehatan Yogyakarta Branch office, such as lower employee self-efficacy / decreased when dealing with consumer complaints, the throwing of responsibilities that resulted in the work of certain people being concentrated, decreased motivation and job satisfaction due to uncertain conditions and ease of work, as well as internal management policies. This has resulted in a decrease in the optimization of services to the community. Objectives: To determine Self-Efficacy, Motivation and Job Satisfaction on Employee Performance BPJS Kesehatan Yogyakarta Branch in 2022. Methods: This type of research is a quantitative method using a certain population and sample, with desain research of cross sectional and this research was carried out at the BPJS Kesehatan Yogyakarta Branch Office. Sampling technique using Total Sampling and a population of 62 employees, correlation analysis used the independent variable and the dependent variable. Conclusion: There is a significant effect between self-efficacy on performance, and there is a significant effect between job satisfaction and performance on employees of BPJS Kesehatan Yogyakarta Branch. Meanwhile, there is no significant influence on the performance of employees of BPJS Yogyakarta Branch.